Analysis of The Effectiveness of Electronic Ticketing Lodaya In Enforcing Traffic Violations - Ramadhan, Raihan Zalfa; ramadhani, arsyi; Yuzafilah, Belby; Gunawan, Moh. Sigit; Karina, Siska (Jurnal Legisci, 2024)
Rampant traffic violations have spurred the development of information system-based technology by the Indonesian National Police equipped with a network or website as its software or Electronic Traffic Law Enforcement (ETLE). Through ETLE Lodaya, people ticketed for traffic violations will be sent a letter. This electronic system is very different from the street's manual ticketing mechanism. This study aims to assess the effectiveness of the ETLE Lodaya system through the mechanism of the Electronic Ticket Lodaya system in the jurisdiction of the Cirebon City Police. The research method used in this writing is qualitative. The data collection technique was conducted by interviewing police members regarding traffic violations at the Cirebon City Police. The results of this study show that the use of Electronic Ticket Lodaya in the Cirebon City Police area has not been effective because of inhibiting factors that affect the effectiveness of the Electronic Ticket system, including the ETLE mechanism, which requires a long process, community disobedience to the rules.